Challenges facing Iranian social security in the path of sustainable development, causes and providing some solutions - Biglary Taleghani, Mohammad; Bagherzadeh, Mohammad Reza; Mehrara, Asdollah; Gholipour-Kanani, Yousef Gholipour-Kanani (Researcher Bulletin of Medical Sciences, 2021)
Following economic, social, political and cultural changes and the spread of social phenomena such as poverty, unemployment, increasing population of the elderly and disabled, governments have taken on new responsibilities towards their citizens and their scope of operation has expanded. (Ghaffari, 2017). In this direction, due to the mentioned changes, several challenges have been faced on social security in relation to the efficient establishment of the social security system. Therefore, the present study, in response to the question of what are the most important challenges of social security in the implementation of sustainable development programs, intends to provide appropriate solutions in this area by analyzing and analyzing the causes of challenges facing the Social Security Organization. This research is a descriptive-comparative type and in addition to interviews with experts, professors and individuals who have researched in the field of social security, as well as a number of managers and experts in the field of social security, using the library method. The statistical population includes existing documents in the field of social security at the domestic and international levels, which have been dictated by reference organizations such as the International Social Security Association (ISSA), International Labour Organization (ILO) and the World Bank in this field. Content analysis method has been used for data analysis. The challenges have been enumerated by adapting the current state of social security to its desired state based on global guidelines, models, and systems. Then, the obtained information was tested using the questionnaire with a reliability coefficient of 0.7 to examine and comment on the experts Delphi test and was analyzed using SPSS software. Findings indicate that social security in Iran is far from global standards and models and is struggling with micro and macro challenges. Evidence and research results showed that the most important reasons for the existing challenges should be pursued in policies, regulations and also in the field of implementation. It also seems that explaining the role of the government in the field of social security is a missing link that ignoring it will jeopardize any orientation in the field of social security and it is necessary to pay attention to macro-planning in this area.